Development of technologies to harness the productivity potential of salt-affected areas of the Indo-Gangetic, Mekong and Nile River basins - Ismail, A.M. (CGIAR Challenge Program on Water and Food, 2009)
This project emphasized the development and deployment of high-yielding salt-tolerant rice varieties and nonrice crops, together with matching management practices, to enhance and sustain system productivity in coastal and inland salt-affected areas. Integrated and participatory approaches were designed and implemented at the research, delivery, and uptake levels to tackle the enormous complexity of challenges in these areas. More intensive and diversified cropping systems were validated to improve farmers’ income and livelihood and preserve the environment. Apparently, tremendous opportunities exist to make use of these marginal resources to meet the rising and pressing demands for food and water.